2009
DOI: 10.1007/s00520-009-0638-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of indicators for patient-centred cancer care

Abstract: Purpose Assessment of current practice with a valid set of indicators is the key to successfully improving the quality of patient-centred care. For improvement purposes, we developed indicators of patient-centred cancer care and tested them on a population of patients with non-small cell lung cancer (NSCLC). Methods Recommendations for patient-centred care were extracted from clinical guidelines, and patients were interviewed to develop indicators for assessing the patientcentredness of cancer care. These indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 35 publications
1
109
0
2
Order By: Relevance
“…This definition was derived from a proposed quality measure that states that therapy should be started within 35 calendar days from the patient's first visit to the pulmonologist. This quality measure was evaluated in prior studies of relatively small cohorts [5,7,8] and proposed as a relevant metric for evaluating care quality in the United States [6]. However, because only 44.7% of patients in our cohort were seen by a pulmonologist within 3 months before diagnosis, we chose to evaluate time from diagnosis to treatment, rather than time from pulmonary consultation to treatment.…”
Section: Guidelines For Timeliness Of Carementioning
confidence: 98%
See 1 more Smart Citation
“…This definition was derived from a proposed quality measure that states that therapy should be started within 35 calendar days from the patient's first visit to the pulmonologist. This quality measure was evaluated in prior studies of relatively small cohorts [5,7,8] and proposed as a relevant metric for evaluating care quality in the United States [6]. However, because only 44.7% of patients in our cohort were seen by a pulmonologist within 3 months before diagnosis, we chose to evaluate time from diagnosis to treatment, rather than time from pulmonary consultation to treatment.…”
Section: Guidelines For Timeliness Of Carementioning
confidence: 98%
“…In addition, studies of PET early in treatment for locoregionally confined NSCLC have shown that these changes in PET are correlated with overall survival in this setting [4]. Thus consensus panels have recommended that treatment be initiated in a timely manner, defined as within 35 days of pulmonary consultation [5][6][7][8]. However, the prevalence, impact, and factors contributing to such delays remain unknown.…”
mentioning
confidence: 97%
“…One of the other main functionalities of indicators is to evaluate and measure performance and the degree to which predetermined goals have been reached [22]. Using literature review, expert panel and Delphi technique to develop the performance indicators was prevalent in previous studies [23][24][25][26]. As indicated in previous studies, Delphi method can be a useful and systematic approach to consensus building about a real subject [13,14,27,28] and facilitate the systematic cycle of indicator development [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the generally poor prognosis, the majority of lung cancer patients undergoes a progressive deterioration in terms of symptom burden or well-being during the course of their disease, as depicted most recently by KOCZYWAS and co-workers [140,141] in their observational studies involving NSCLC stage I-III (n=103) as well as NSCLC stage IV patients (n=114) over a period of up to 1 year. Thus, outcome analyses for lung cancer patients have already been extended far beyond sole survival or relapse data acquisition [142][143][144][145][146][147][148]. Nonetheless, due to its complexity, thriving research of palliative care scientific questions cannot be based on classical clinical trial designs alone but needs an enhanced methodological repertoire, such as quality of care and quality improvement research approaches [149][150][151][152][153][154].…”
Section: Barriers For Integration Of Palliative Care Into Routine Lunmentioning
confidence: 99%